Genome sequences of two pathogenic Streptococcus agalactiae isolates from the one-humped camel Camelus dromedarius - Zubair, S.; Villiers, Etienne P. de; Younan, M.; Andersson, G.; Tettelin, H.; Riley, D.R.; Jores, Joerg; Bongcam-Rudloff, E.; Bishop, Richard P. (American Society for Microbiology, 2013)
Streptococcus agalactiae causes a range of clinical syndromes in camels ( Camelus dromedarius ). We report the genome sequences of two S. agalactiae isolates that induce abscesses in Kenyan camels. These genomes provide novel data on the composition of the S. agalactiae “pan genome” and reveal the presence of multiple genomic islands.